2020
DOI: 10.15625/2525-2518/58/4/14856
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds and Biological Activities of Essential Oil of Globba Pendula Roxb. Collected at an Giang Province

Abstract: Twenty-five compounds were identified from the essential oil of Globba pendula Roxb. by gas chromatography–mass spectrometry (GC-MS) with Selinene<d-> (22.09%) as the main component, followed by Ishwarane (6.52%). The essential oil was found to possess moderate NO inhibitory effect with IC50 of 41.68 ±4.51 µg/ml, significant cytotoxic activity against MCF7 and Hep3B cell lines with IC50 of 28.15±1.08 and 35.24±0.06 (µg/ml), respectively. This is the first report on volatile compounds and biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Nevertheless, they can be deduced from the properties of other EOs, where this terpene predominates with an amount like the one of N. laurel. Three species were identified that produce an EO with these features: Jatropha elliptica rhizomes (Euphorbiaceae) from Brazil, Globba pendula rhizomes (Zingiberaceae) from Indochina, and Xanthium italicum flowers (Asteraceae) from Corsica [59][60][61]. The amount of δ-selinene in the volatile fraction of these plants was 35.7%, 36.4%, and 22.4%, respectively; however, only for G. pendula EO were biological activities investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, they can be deduced from the properties of other EOs, where this terpene predominates with an amount like the one of N. laurel. Three species were identified that produce an EO with these features: Jatropha elliptica rhizomes (Euphorbiaceae) from Brazil, Globba pendula rhizomes (Zingiberaceae) from Indochina, and Xanthium italicum flowers (Asteraceae) from Corsica [59][60][61]. The amount of δ-selinene in the volatile fraction of these plants was 35.7%, 36.4%, and 22.4%, respectively; however, only for G. pendula EO were biological activities investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of δ-selinene in the volatile fraction of these plants was 35.7%, 36.4%, and 22.4%, respectively; however, only for G. pendula EO were biological activities investigated. In this case, the oil showed a moderate inhibitory capacity on NO production in LPS-activated macrophages, with an IC 50 = 41.68 ± 4.51% versus 6.51 ± 0.31% of the positive control (NG-methyl-L-arginine acetate) [ 60 ]. The same EO also showed a moderate in vitro cytotoxic activity against Hep3B (human hepatoma) and MCF7 (human breast carcinoma) cell lines, with an IC 50 of 35.24 ± 0.06% and 28.15 ± 1.08%, respectively versus 0.59 ± 0.19% and 6.46 ± 0.81% for the positive control (camptothecin) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The essential oil of this plant was found to possess moderate NO inhibitory effect, and significant cytotoxic activity against MCF7 and Hep3B cells. 4 We previously reported the isolation of one new polyoxygenated cyclohexene, globbanol A (1), along with two other cyclohexene derivatives, crotepoxide (2) and boesenboxide (3), and a chalcone, 2 ′ -4,4 ′ ,6 ′ -trimethoxychalcone (4), from the ethyl acetate extract of the rhizomes of G. pendula. 5 In this study, various extracts of G. pendula rhizomes were screened for in vitro anti-inflammatory activity on lipopolysaccharide-stimulated RAW 264.7 macrophages.…”
Section: Introductionmentioning
confidence: 99%